TROJANUS : An ultra-lightweight side-channel leakage generator for FPGAs - Kutzner, Sebastian (2014)
In this article we present a new side-channel building block for FPGAs, which, akin to the old Roman god of Janus, has two contradictory faces: as a watermarking tool, it allows to uniquely identify IP cores by adding a single slice to the design; as a Trojan Side-Channel (TSC) it can potentially leak an entire encryption key within only one trace and without the knowledge of either the plaintext or the ciphertext. We practically verify TROJANUS' feasibility by embedding it as a TSC into a lightweight FPGA implementation of PRESENT. Besides, we investigate the leakage behavior of FPGAs in more detail and present a new pre-processing technique, which can potentially increase the correlation coefficient of DPA attacks.